MENINGKATKAN PERCAYA DIRI BERBICARA BAHASA INGGRIS DI CAHAYA ANAK NEGERI BEKASI - Enny Diah Astuti; Retno Setya Budiasningrum; Rahmi Rosita; Dyan Yuliana; Jajang Setiawan; Ali Satri Efendi (Fakultas Teknik Universitas Cenderawasih, 2022)
Self-confidence is a very important aspect for a person to develop his potential. The higher the confidence to speak in English, the smoother it will be to get the expected results. If you liken it, self-confidence is a key to open the door of doubt that has been a hindrance when you are trying to find a way out. The training method carried out is adjusted to the goal to be achieved, namely to increase self-confidence in speaking English. According to the needs of children, the material that needs to be developed at the Bekasi State Children's Light Community Service place was chosen, the theme